Optimalisasi dan Penyelesaian Job Shop Scheduling Problem dengan Metode Algoritma Genetik (Studi Kasus Injection Mould Base Tumbler Upper Cap di PT. Berlina Tbk Pandaan, Pasuruan) - Niko Aditya; Rina Sandora; Endang Pudji Purwanti (Proceedings Conference On Design Manufacture Engineering And Its Application, 2020)
PT. Berlina Tbk Pandaan is a plastic packaging and mold maker company with a make to order production system especially at the Mold Shop Department with job shop production flow. From the scheduling system, production delays often occur. Injection Mold Base for Tumbler Upper Cap products was chosen as the object of research with a delay of 7 weeks. The purpose of this study is to determine the sequence of job operations flow by minimizing tardiness and makespan using the Genetic Algorithm method so as to produce optimum scheduling. The analysis of this study involved 37 jobs with 24 different machines. Calculations on the Genetic Algorithm method using Microsoft Excel and MATLAB R2012b media. From the calculation of the Genetic Algorithm method produces tardiness value of 0 hours, makespan 134.125 hours, and the highest fitness value of 2.3126. While scheduling the company produces a value of tardiness of 589.8750 hours and makespan of 195.125 hours. Then this method is able to minimize 100% tardiness and 31% makespan of company scheduling. While the operating flow of the resulting job is: 25-14-11-26-6-18-23-36-31-5-4-1-13-33- 8-35-32-12-34-7-3- 28-17-15-29-2-22-27-9-30-19-21-37-16-24-20-10.